A liberal theory of property / Hanoch Dagan, Tel Aviv University. - Dagan, Ḥanokh (Cambridge University Press, 2021)
Property enhances autonomy for most people, but not for all. Because it both empowers and disables, property requires constant vigilance. A Liberal Theory of Property addresses key questions: how can property be justified? What core values should property law advance, and how do those values interrelate? How is a liberal state obligated to act when shaping property law? In a liberal polity, the primary commitment to individual autonomy dominates the justification of property, founding it on three pillars: carefully delineated private authority, structural (but not value) pluralism, and relational justice. A genuinely liberal property law meets the legitimacy challenge confronting property by expanding people's opportunities for individual and collective self-determination while carefully restricting their options of interpersonal domination. The book shows how the three pillars of liberal property account for core features of existing property systems, provide a normative vocabulary for evaluating central doctrines, and offer directions for urgent reforms.